Peranan Internal Audit dalam Menunjang Efektivitas Sistem Pengendalian Intern padaPT XYZ - Bu, Kwang (Jurnal Ilmiah Ranggagading (JIR), 2006)
The implementation of system and procedure of remuneration control and the role of internal audit at a firm is extremely vital to minimize deceit inflicting losses of the firm. Besides, internal control of remuneration plays a very important role in increasing employeeâs motivation, so that they work more effectively and have significant influence towards work moral and discipline. Therefore, it is necessary to be managed well to avoid employeeâs disappointment. The result of research concluded that internal audit has significant influence to the effectiveness of internal control of remuneration system at the firm. It was proven when internal supervisor carried out evaluation at general department responsible to time recording and prepared payroll, it was found out false working time account and fictitious employee payroll. Keywords: Internal Control System; remuneration